Influence of walking football on decreasing cholesterol and blood glycemic level - Siswantoyo Siswantoyo; Kukuh Hardopo Putro; Japhet Ndayisenga; Rajesh Kumar; Rozita Abdul Latif (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
The aims of this research to determine the impact of walking football on cholesterol and glycemic management in order to allow people to live healthily. This research is an experimental study with quantitative approach. The research sampling was 12 subjects from different category: (1) International students, (2) Local students, and employed persons. Technique collecting data using playground of futsal to assess variables like glycemic and cholesterol. Data analysis using independent test sample. To evaluate the subjects’ health condition, the research proceeded by pre-test first, for the second step a walking football was given during 12 weeks within 3 times per week. After the training a posttest has been provided to check the improvement of the subject’s health. The result showed that there is a strong different between pre-test and posttest on glycemic level with P (0.000) inferior to 0.05. Second there was a significant different from pre-test and posttest cholesterol data within P (0.000) inferior to 0.05. The walking football is a strong tool to help people at the different age to maintain their good condition but also to allow good performance for athletes. Walking football is very easy to apply and provide happiness